Pathways to Drug Dealing in the Middle and Upper Classes: early Marginalization, Relative Disadvantage and Countercultural Opposition - Berger, Eirik Jerven (The British journal of criminology, 2023)
Drug dealing is widespread in all sectors of society but is still studied predominantly in disadvantaged urban areas. We identify three main pathways to drug dealing based on qualitative interviews with middle- and upper-class individuals in Oslo, Norway. First, problems in the family and school and a lack of belonging in affluent neighbourhoods intersected with drug use and eventually led to recruitment into the illegal drug economy. Second, criminal entrepreneurship developed among relatively disadvantaged people who dealt drugs in an affluent low-risk context. Third, dealing emerged from involvement in drug liberalization and medical marihuana countercultures. The first pathway is similar to trajectories in disadvantaged urban areas, while the others reveal the importance of studying drug dealing in the upper layers of society.